PERBANDINGAN PENGGUNAAN SEMEN DAN GARAM UNTUK STABILISASI TANAH DASAR - Zuhrufah Diana Azza, Gerard Aponno, Dwi Ratnaningsih (Prokons: Jurnal Teknik Sipil, 2019)
Soil is the key of the road foundations. Soil of high CBR value will have good bearing capacity for road construction. Conversely, soil stabilization must be carried out to the subgrade that has bad bearing capacity. The goals of this analysis are to find out the soil characteristict of before stabilization, CBR values of before and after stabilization, the optimum cement use and salt (NaCl) use as stabilizers.The results of soil poperties test in Silt High Plasticity (MH) based on Unified Soil Classification System (USCS) and A-7-5 based on American Association of State Highway and Transportation Official (AASHTO). The result of CBR without stabilization is 3.64% for standard soaked and 5.13%  for modified soaked. The maximum results of stabilized testing with cement showed 9.802 % CBR; 69.298% CBR of each sample respectively standard and modified soaked test; of salt showed 3.93% CBR; 5.33% CBR of standard and modified soaked test of each sample respectively.   Keywords: CBR, cement, NaCl, soil stabilization